Prospective study of gestational diabetes and fatty liver scores 9 to 16 years after pregnancy. Issue 11 (12th June 2019) - Donnelly, Sarah R.; Hinkle, Stefanie N.; Rawal, Shristi; Grunnet, Louise G.; Chavarro, Jorge E.; Vaag, Allan; Wu, Jing; Damm, Peter; Mills, James L.; Li, Mengying; Bjerregaard, Anne A.; Thuesen, Anne Cathrine B.; et al.
Abstract: Background: Women with gestational diabetes mellitus (GDM) may be at an increased risk of liver complications because chronic hyperglycemia is a risk factor for liver fat accumulation and potential liver dysfunction. Large prospective studies examining liver fat accumulation following a GDM pregnancy are lacking. Methods: The Diabetes & Women's Health Study (2012‐2014) examined the association between GDM and subsequent fatty liver scores among 607 women with and 619 women without GDM in the Danish National Birth Cohort. Nine to 16 years postpartum, a clinical examination was performed, with measurement of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and γ‐glutamyl transferase, from which fatty liver scoring indices were calculated to assess liver fat score, fatty liver index, hepatic steatosis index, and liver fat percentage. Relative risks (RR) with 95% confidence intervals (CI) for elevated liver scoring indices by GDM status were assessed adjusting for major risk factors, including prepregnancy body mass index. Results: Women with prior GDM had higher adjusted ALT and AST levels than women without GDM (by 6.7% [95% CI 1.7‐12.0] and 4.8% [95% CI 0.6‐9.1], respectively). Women with GDM also had adjusted increased risks for elevated liver fat score (RR 2.34; 95% CI 1.68‐3.27), fatty liver index (RR 1.59; 95% CI 1.27‐1.99), and hepatic steatosis index (RR 1.44; 95% CI 1.21‐1.71). Conclusions: Women with GDM during pregnancy were at an increased risk for fatty liver 9 to 16 years postpartum. Gestational diabetes mellitus may serve as another risk indicator for the early identification and prevention of liver fat accumulation. Abstract : Highlights Liver scoring indices were significantly elevated in women with gestational diabetes 9 to 16 years after the index pregnancy. Alanine aminotransferase and aspartate aminotransferase levels were higher and liver fat percentage was greater in women with than without gestational diabetes. Women with gestational diabetes may be at a higher risk for liver fat accumulation, regardless of and prior to the development of overt diabetes later in life. 摘要: 背景: 妊娠期糖尿病(gestational diabetes mellitus，GDM)女性发生肝脏并发症的风险可能增加，因为慢性高血糖是肝脏脂肪蓄积及潜在肝功能异常的危险因素。目前评估GDM患者产后肝脏脂肪蓄积的大型前瞻性研究不足。 方法: 糖尿病与女性健康研究(The Diabetes & Women's Health Study, 2012‐2014)使用丹麦国家出生队列，在607例合并GDM的女性和619例无GDM的女性中调查了GDM与后续脂肪肝评分之间的相关性。在产后9‐16年进行临床检查，测定丙氨酸氨基转移酶(alanine aminotransferase，ALT)、天冬氨酸氨基转移酶(aspartate aminotransferase，AST)和γ‐谷氨酰转移酶，由此计算脂肪肝评分指标，评估肝脏脂肪评分、脂肪肝指数、肝脏脂肪变性指数以及肝脏脂肪百分比。校正主要风险因素(包括妊娠前体重指数)后，根据GDM状态评估导致肝脏评分指标升高的相对风险(relative risk，RR)及其95%可信区间(confidence interval，CI)。 结果: 既往患GDM的女性校正的ALT及AST水平均高于无GDM的女性(分别高出6.7%[95% CI: 1.7‐12.0]与4.8%[95% CI: 0.6‐9.1])。GDM女性的校正后肝脏脂肪评分(RR 2.34；95% CI: 1.68‐3.27)、脂肪肝指数(RR 1.59；95% CI: 1.27‐1.99)及肝脏脂肪变性指数(RR 1.44；95% CI: 1.21‐1.71)升高的风险也增加。 结论: 妊娠期合并GDM的女性在产后9‐16年发生脂肪肝的风险增加。GDM可作为早期发现和预防肝脏脂肪蓄积的另一个风险指标。